2018
DOI: 10.1016/j.nedt.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence among nursing students: Findings from a cross-sectional study

Abstract: Emotional intelligence was higher in nursing than engineering students, and slightly higher in women than men. It was not associated with previous caring experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 28 publications
3
28
0
8
Order By: Relevance
“…Furthermore, providing a wide range of instruments and tools to nurses for ongoing self‐monitoring and self‐evaluation is crucial to prevent and lower the incidence of burnout, aggression and patient neglect among the nurse workforce (Beech & Leather, ; McNamara, ). Staff welfare programmes should be put in place aimed at enhancing health care and well‐being in this professional category and should consider individual differences in personality traits, such as impulsivity and aggression, empathy and emotion regulation as potential risk and protective factors (Por et al., ; Song et al., ; Štiglic et al., ). Gender should also be considered as an important factor, considering that nursing is a predominantly female workforce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, providing a wide range of instruments and tools to nurses for ongoing self‐monitoring and self‐evaluation is crucial to prevent and lower the incidence of burnout, aggression and patient neglect among the nurse workforce (Beech & Leather, ; McNamara, ). Staff welfare programmes should be put in place aimed at enhancing health care and well‐being in this professional category and should consider individual differences in personality traits, such as impulsivity and aggression, empathy and emotion regulation as potential risk and protective factors (Por et al., ; Song et al., ; Štiglic et al., ). Gender should also be considered as an important factor, considering that nursing is a predominantly female workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in healthcare profession, empathy and emotional intelligence in general may represent a protective trait to efficiently cope with stressful situations. Indeed, a recent study (Štiglic et al., ) found that emotional intelligence was higher in nursing than engineering students and slightly higher in women than men. How levels of aggression interact with gender, individual traits and characteristics of emotional stimuli in the nursing context remains unaddressed by current research.…”
Section: Introductionmentioning
confidence: 98%
“…However, ST and OT students only see these practices as a means for learning about anatomical structures. In addition, NUR students have greater training in empathy and emotional intelligence, with their roles being associated with compassion and care [37][38][39][40], which could explain their greater empathy towards the cadaver and their greater anxiety both before and after the practice. MED and NUR students may have given greater thought to death and its meaning due to their roles, and the acceptance of these and derived issues, such as concerns about the brevity of life and uncertainty about what happens after death, may increase their anxiety [39,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…[18] Therefore, the nurse educators should ensure that nursing student has a high level of EI at the point of graduation from nursing program. [15,19] Moreover, EI should be learned and developed during clinical training in the undergraduate training program and there is general evidence that EI can be improved with training. [20,21] 1.1 Significance of the study During the student clinical rotation in the burn ICU at Tanta Emergency Hospital, it was found that a great number of second year nursing students emotionally disturbed when they became contact with severe burns injured patient and unable to provide a high quality of care.…”
Section: Introductionmentioning
confidence: 99%